1989
DOI: 10.1002/ajmg.1320320322
|View full text |Cite
|
Sign up to set email alerts
|

A presumptive translocation 1p;2q resulting in duplication 1p and deletion 2q

Abstract: Here we report on a girl with a translocation between 1 and 2 and duplication 1p and deletion 2q resulting in a multiple congenital anomaly syndrome including intrauterine growth retardation, microcephaly, hypotelorism, cleft palate, subglottic stenosis, umbilical hernia, scoliosis, anal atresia, bilateral calcaneovalgus, overlapping toes, and vertebral anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…Halal et al 46 described a female infant with trisomy 1p31-1pter, resulting from a translocation between chromosomes 1 and 2. It is likely that one of the parents (who refused testing) carries a balanced translocation, as there were seven previous miscarriages.…”
Section: Mapping Of Trisomic Regions In Partial Trisomiesmentioning
confidence: 99%
“…Halal et al 46 described a female infant with trisomy 1p31-1pter, resulting from a translocation between chromosomes 1 and 2. It is likely that one of the parents (who refused testing) carries a balanced translocation, as there were seven previous miscarriages.…”
Section: Mapping Of Trisomic Regions In Partial Trisomiesmentioning
confidence: 99%
“…1B). The 1p duplications identified by Elejalde et al [1984], Halal et al [1989], and Warden et al [2001] completely overlap the 1p duplication identified in our patient. Thus the telomeric breakpoint of the 1p duplication reported by Garcia-Heras et al [1999] and the telomeric breakpoint identified in our patient possibly narrow the region of dosage sensitivity for congenital heart defects on 1p (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…1B). A patient, from Halal et al [1989] had a large duplication of 1p (from 1p31 to 1pter) that completely covers the duplication identified in our patient; however, this patient also had a deletion on chromosome 2q through inheritance of an unbalanced translocation. This patient had intrauterine growth retardation, multiple congenital heart defects and growth retardation and died at 3 months.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations